Comparison of Laboratory Examination Results and Clinical Manifestations In Post Chemotherapy Folfox Regimens and Capeox Regimens In Colorectal Cancer Patients at Ibnu Sina Educational Hospital Umi Wakaf Foundation Macassar - Miftahul Jannah; Syamsu Rijal; Nur Aulia; Sri Julyani; Berry Erida Hasbi (International Journal of Health and Pharmaceutical (IJHP), 2025)
Colorectal cancer (CRC) is the fourth leading cause of death in the world, often associated with an unhealthy diet, including low consumption of fruits, vegetables, and fiber, and high intake of red meat. This study aims to compare the results of laboratory examinations and clinical manifestations in patients undergoing chemotherapy using Folfox and CapeOX regimens at Ibnu Sina Teaching Hospital, UMI Waqf Foundation, Makassar. The method used was descriptive design with cross-sectional approach and purposive sampling technique. The results showed that in Folfox regimen chemotherapy patients, there were 90.9% with low erythrocytes and 95.5% with low hemoglobin, while in CapeOX regimen, 59.1% of patients had low erythrocytes. Of the 22 patients in each regimen, 14 patients (Folfox) and 9 patients (CapeOX) reported complaints. Comparison of leukocyte examination between the two regimens showed a significant association with a p-value of 0.044 (p<0.05), while examination of erythrocytes, platelets, hemoglobin, blood sugar, and clinical manifestations did not show a significant association (p>0.05). This study provides insight into the impact of each chemotherapy regimen on the patient's condition.